Effectiveness of 3% Clove Leaf Extract Ointment (Syzygium Aromaticum) with Sodium Saccharin on Wound Healing - Hendri Poernomo; Setiawan; Sebastian Pernando Hiro (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: Wound healing requires a complex process, involving biocellular and biochemical responses, as well as the formation of new tissue to restore bodily functions such as fibroblast production. Clove leaves (Syzygium aromaticum) contain active compounds such as tannins, flavonoids, and eugenol, which can help reduce inflammation and support new tissue formation. The purpose of this study was to test the effectiveness of a 3% clove leaf extract ointment combined with Sodium saccharin. Material and Methods: This was an in vivo experimental study using a post-test only control group design. Thirty male Wistar rats (Rattus norvegicus) aged 2-3 months with a body weight of 150-200 grams were randomly selected. The samples were divided into three treatment groups, namely negative control (Adeps lanae and Vaseline album), positive control (Enbatic ointment), and treatment group (3% clove leaf extract ointment with Sodium saccharin). An incision was made on the back of each rat, and then they were given treatment for 7 days. The number of fibroblasts was observed using a microscope with hematoxylin-eosin staining. Data analysis used a one-way ANOVA test. Results and Discussions: Administration of 3% clove leaf extract ointment with Sodium saccharin can increase the number of fibroblasts compared to negative controls and positive controls. The results of the ANOVA analysis showed a significant difference between the treatment group, positive control, and negative control (p < 0.05). This means that the ointment formulation provides better results in supporting wound healing compared to the control treatment. Sodium saccharin increases the comfort of using the ointment, also showing that its effectiveness is not significantly different compared to 3% clove leaf extract ointment without addition. Conclusion: A concentration 3% of clove leaf extract (Syzygium aromaticum) ointment supplemented with Sodium saccharin is more effective in increasing the number of fibroblast cells.